2017
DOI: 10.1016/j.psyneuen.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

BXD recombinant inbred strains participate in social preference, anxiety and depression behaviors along sex-differences in cytokines and tactile allodynia

Abstract: Depression and anxiety are the most common psychiatric disorders, representing a major public health concern. Dysregulation of oxidative and inflammatory systems may be associated with psychiatric disorders, such as depression and anxiety. Due to the need to find appropriate animal models to the understanding of such disorders, we queried whether 2 BXD recombinant inbred (RI) mice strains (BXD21/TyJ RI and BXD84/RwwJ RI mice) and C57BL/6 wild-type mice show differential performance in depression and anxiety re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Increased serum levels of TNF-α and IL-6 have been shown in two different BXD mouse lineages that are commonly used as genetic resources to study neuropharmacological phenomenon (Philip et al, 2010). In BXD21/TyJ RI mice, nuclear factor erythroid 2 (Nrf2) expression is upregulated, while BXD84/RwwJ RI mice exhibit low Nrf2 expression (López-Granero et al, 2017). Considering the role of Nrf2 in activating antioxidative mechanisms (Zhang et al, 2013), these mice show greater depressive-like behavior than wild-type mice (López-Granero et al, 2017).…”
Section: Target Structures Involved In Pain and Depressionmentioning
confidence: 99%
“…Increased serum levels of TNF-α and IL-6 have been shown in two different BXD mouse lineages that are commonly used as genetic resources to study neuropharmacological phenomenon (Philip et al, 2010). In BXD21/TyJ RI mice, nuclear factor erythroid 2 (Nrf2) expression is upregulated, while BXD84/RwwJ RI mice exhibit low Nrf2 expression (López-Granero et al, 2017). Considering the role of Nrf2 in activating antioxidative mechanisms (Zhang et al, 2013), these mice show greater depressive-like behavior than wild-type mice (López-Granero et al, 2017).…”
Section: Target Structures Involved In Pain and Depressionmentioning
confidence: 99%
“…Previously, we have demonstrated that certain inflammatory responses could be desirable in mitigating psychiatric disorders, such as depressive behavior. We have observed that the BXD21/TyJ strain exhibited lessened immobility time in the forced swim test, congruent with lessened depression-like behavior 20 . Concomitantly, we noted overexpression of cerebral cortex proinflammatory cytokines, (tumor necrosis factor alpha (TNFα) and interleukin 6 (IL-6)) in the absence of oxidative stress 20 .…”
mentioning
confidence: 53%
“…Here, we chose the BXD84/RwwJ RI and BXD21/TyJ strains given their diverse expression lof Nrf2 mRNA. In an earlier report, we have demonstrated low expression of Nrf2 mRNA in the BXD84/RwwJRI strain and its high expression in BXD21/TyJ RI strain at postnatal day 21 20 . Since the BXD RI mouse strains and Nrf2 might offer an optimal platform for relating genetic influences with environmental exposure outcomes, the understanding of the relationship between BXD RI mice and Nrf2 is essential.…”
mentioning
confidence: 66%
See 2 more Smart Citations